Specific Primer Design and Optimization of Monodehydroascorbate reductase (MDHAR) Gene Amplification in Rice (Oryza sativa L.) - Jumatul Hafsah; Afifatul Achyar; Zulyusri; Yusni Atifah; Linda Advinda; Violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Monodehydroascorbate reductase (MDHAR) is an enzyme responsible for growth and response to biotic and abiotic stress. MDHAR in rice shows a higher sensitivity to stress compared to other plants. This study aims to obtain specific primers for the MDHAR gene in rice to be used in PCR amplification so that it can amplify the MDHAR gene. Primers are designed using the Pickprimer and Geneious Primer tools. Optimization of annealing temperature was carried out using the gradient PCR method and then an in vitro primary specification test was carried out using the Touchdown PCR method. The results of the primary design obtained one candidate primer that met the ideal primer requirements, namely a pair of primers (5'-AAAAACACTGCATGGGTCGTC-3' and 5'-CGCCTACCGTTTCCCAAGTT-3') with an amplicon length of 160 bp. The visualization results of PCR products using 1.5% agarose showed that 6 samples were able to amplify the MDHAR gene at 160 bp in size. However, in each lane there is a non-specific DNA band (Primer dimer). In vitro primer specification testing with Touchdown succeeded in increasing product formation specifications and was able to reduce non-specific DNA bands (Primer dimers).